2017
DOI: 10.1016/j.landusepol.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Forest transitions in Chinese villages: Explaining community-level variation under the returning forest to farmland program

Abstract: China's Returning Farmland to Forest Program (RFFP) aimed to transform rural landscapes and livelihoods by compensating households for planting trees on retired farmland. The program has been attributed a key role in an apparent forest transition. Studies uncover great local variation in its impacts, but the mechanisms behind them have received little attention. We examine such heterogeneity in 12 communities in northwest Yunnan, assessing the hypothesis that the RFFP catalyzed a state-led forest transition by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 75 publications
0
30
0
Order By: Relevance
“…Over this period, significant land conversion into forests occurred, resulting in an increase of forest coverage [39]. This effect is likely in response to current policy which focused on restoring cultivated land to forests in China [40][41][42]. Fan et al (2019) further confirmed that the forested areas in the Nanping City has increased, while the area of cultivated land has decreased from 2010 to 2015 [43].…”
Section: The Lucc Between 2014 and 2017mentioning
confidence: 82%
“…Over this period, significant land conversion into forests occurred, resulting in an increase of forest coverage [39]. This effect is likely in response to current policy which focused on restoring cultivated land to forests in China [40][41][42]. Fan et al (2019) further confirmed that the forested areas in the Nanping City has increased, while the area of cultivated land has decreased from 2010 to 2015 [43].…”
Section: The Lucc Between 2014 and 2017mentioning
confidence: 82%
“…By 2010, the "linking villages with roads" program was implemented. Roads brought connectivity between communities and markets that facilitated walnut production [38,43]. Other changes in livelihoods during this period include the adoption of cash crops such as runner beans, maca, and costus root, as well as increasing off-farm labor allocation, varying in magnitude across communities.…”
Section: Discussionmentioning
confidence: 99%
“…During the past 30 years, policy has always played a critical role in China's social-economic development [115], which is the same regarding its impacts on household energy consumption. Key policies that are driving the household energy consumption in China mainly include the "new normal urbanization policy" [113,114], "returning farmland to forests/grasses program" [116], "natural forest protection program" [117], and "grazing prohibition and enclosure" [64,118], which mainly reduce the biomass energy consumption in China, particularly in the north and northwestern rural regions, and "rural electrification program" [119] which mainly improves the shares of the electricity consumption in rural China. Internationally, these policies could offer good experiences for other developing countries, for instance, the Chinese model of rural electrification projects could serve as an inspiration for other developing countries [120].…”
Section: Driving Forces: Determinants and Performancementioning
confidence: 99%